2009
DOI: 10.1017/s1368980009004996
|View full text |Cite
|
Sign up to set email alerts
|

Meal patterns among children and adolescents and their associations with weight status and parental characteristics

Abstract: Objectives: To describe the meal patterns of Jena schoolchildren and their associations with children's weight status and parental characteristics. Design: Cross-sectional study. Setting: Twenty schools in Jena ( ,100 000 inhabitants), south-east Germany. Subjects: A total of 2054 schoolchildren aged 7-14 years with information on BMI standard deviation score (BMI-SDS) and weight status (based on German reference values), of whom 1571 had additional information about their parents (parental education and emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 30 publications
6
38
2
Order By: Relevance
“…As in the present study, previous results on school lunch consumption relative to weight status have mostly shown no relationship (16)(17)(18)(19)(20) . Previous studies that focus only on dinner are lacking.…”
Section: Discussioncontrasting
confidence: 70%
“…As in the present study, previous results on school lunch consumption relative to weight status have mostly shown no relationship (16)(17)(18)(19)(20) . Previous studies that focus only on dinner are lacking.…”
Section: Discussioncontrasting
confidence: 70%
“…The increased focus on the importance of regular meals may positively have influenced the finding of no changes in meal patterns during 8 years in the present study. Breakfast represents a healthy habit and associations with positive health outcomes have been widely described (20) , ranging from reduced prevalence of overweight (21) via improved dietary quality (1) to -'All meals' includes a sum score of whether breakfast, lunch, dinner and supper was eaten yesterday. Variable is dichotomized into having fewer than 4 meals per day and having 4 meals per day.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between overweight and meal frequency is still debated; some have found that skipping meals yields higher odds of being overweight (5,11,21) , while others have not detected significant associations (2) . Among the children living with only one parent, there were more breakfast and lunch skippers compared with those living with two parents.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a second child in the family was found to be associated with a decrease in the average diet quality score in the age-specific analyses that included both-parent families only and also in analysis of cumulative effects of mothers working full time on adolescent diet quality at (8,11,(30)(31)(32)(33)(34) . By examining the relationship between parental employment status and weekly working hours prospectively, our age-specific analysis has revealed that having mothers stay home in the first three to five years of life was beneficial to their child's diet quality in adolescence.…”
Section: Discussionmentioning
confidence: 97%